IMPROVING SURGICAL RESULTS OF ANTIPARASITIC TREATMENT OF RESIDUAL CAVITY OF ECHINOCOCCAL CYST IN THE LIVER - Nabiev I. M.; Khozhimetov D. Sh.; Aliboev M. R. (Web of Journals Publishing, 2025)
Echinococcosis is still a serious problem today. Cystic echinococcosis (CE) is an endemic helminthic disease caused by infection with metacestodes (larval stage) of the tapeworm Echinococcus granulosus. Echinococcosis is more common in Australia, North and East Africa, Central Asia and some Mediterranean countries. Analysis of the literature data has shown that the problem of echinococcosis is still very relevant, especially in endemic regions, and, unfortunately, one of the current problems of surgical treatment of liver echinococcosis is still the prevention of relapses of the disease. There are still both residualand recurrent forms of the disease, despite the fact that many methods of treatment of the residual cavity, methods of pre-and postoperative chemoprophylaxis with mebendazole derivatives have been developed. However, only strict adherence to the protocol of preserving operations, their implementation in specialized hospitals and mandatory antiparasitic therapy with albendazole will bring success to minimally invasive surgery for liver echinococcosis.
Keywords: Echinococcosis, experimental part,laser surgery, interventional radiology.